2001
DOI: 10.1073/pnas.98.3.1249
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor and dopamine receptors are required in Δ 9 -tetrahydrocannabinol modulation of sexual receptivity in female rats

Abstract: Ovarian steroids, estrogen and progesterone, influence the sensitivity of certain neural processes to cannabinoid treatment by modulation of brain dopaminergic activity. We examined the effects of the active ingredient of cannabis, ⌬ 9 -tetrahydrocannabinol (THC), on sexual behavior in female rats and its influence on steroid hormone receptors and neurotransmitters in the facilitation of sexual receptivity. Our results revealed that the facilitatory effect of THC was inhibited by antagonists to both progestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 51 publications
1
42
1
1
Order By: Relevance
“…These factors may account, in part, for the effects of marijuana and THC on secretion of gonadotrophic hormones and gonadal steroids, sperm production, ovulation, mating behavior, sperm capacitation, fertilization, early embryonic development; implantation of blastocysts into the uterine endometrium, placental functions, fetal growth, number of pregnancies carried to term, postnatal development, tumor growth, etc. (Powell and Fuller, 1983;Maykut, 1985;Smith and Asch, 1987;Astley and Little, 1990;Murphy et al, 1994;Maccarrone et al, 2000;Fried and Smith, 2001;Paria and Dey, 2000;Mani et al, 2001;Paria et al, 2001;Schuel et al, 2002). Collectively, these observations suggest that endocannabinoids may be normal physiological constituents of human reproductive fluids.…”
Section: Introductionmentioning
confidence: 78%
“…These factors may account, in part, for the effects of marijuana and THC on secretion of gonadotrophic hormones and gonadal steroids, sperm production, ovulation, mating behavior, sperm capacitation, fertilization, early embryonic development; implantation of blastocysts into the uterine endometrium, placental functions, fetal growth, number of pregnancies carried to term, postnatal development, tumor growth, etc. (Powell and Fuller, 1983;Maykut, 1985;Smith and Asch, 1987;Astley and Little, 1990;Murphy et al, 1994;Maccarrone et al, 2000;Fried and Smith, 2001;Paria and Dey, 2000;Mani et al, 2001;Paria et al, 2001;Schuel et al, 2002). Collectively, these observations suggest that endocannabinoids may be normal physiological constituents of human reproductive fluids.…”
Section: Introductionmentioning
confidence: 78%
“…Similarly, our results imply that addition of exogenous cannabinoids from marijuana smoke may flood endogenous AEA-signal systems in female reproductive tracts, thereby impacting fertility in women who abuse marijuana. Consequently, our study has potential ramifications for clinical medicine and public policy because of marijuana abuse in our society (Turner et al, 1998), known effects of cannabinoids on reproductive functions (Powell and Fuller, 1983;Smith and Asch, 1987;Murphy et al, 1994;Schuel et al, 1999;Paria and Dey, 2000;Mani et al, 2001;Paria et al, 2001), and ongoing debates about medicinal use of marijuana.…”
Section: Discussionmentioning
confidence: 99%
“…THC and/or AEA affect all reproductive functions studied thus far, including: secretion of pituitary gonadotrophic hormones and gonadal steroids; sperm production; ovulation; mating behavior; early embryonic development; implantation of blastocysts into the uterine endometrium; fetal growth; number of pregnancies carried to term, etc. (Powell and Fuller, 1983;Maykut, 1985;Smith and Asch, 1987;Murphy et al, 1994;Schuel et al, 1999;Maccarrone et al, 2000;Paria and Dey, 2000;Mani et al, 2001;Paria et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using tissue culture systems have revealed that PRs as well as some other nuclear receptors can be activated in a ligand-independent manner by stimuli that modulate intracellular kinase activity (Denner et al 1990, Aronica & Katzenellenbogen 1991, Beck et al 1993, Sartorius et al 1993. The physiological relevance of a progesterone-independent mechanism of receptor activation has been substantiated in vivo: PR-mediated lordosis behavior exhibited by rats (Mani et al 2001) and mice (Mani et al 1996) can be stimulated either in response to progesterone or in the absence of progesterone by dopamine-activated intracellular signaling pathways.…”
mentioning
confidence: 99%